BPEL PM and OSB operational management with Oracle Enterprise Manager 10g Grid Control : manage the operational tasks for multiple BPEL and OSB environments centrally - Bharadwaj, Narayan (Packt Pub., 2010)
Annotation In the SOA world, managing distributed services and service infrastructures is critical. Oracle Enterprise Manager _ an all-encompassing management product _ facilitates increased management capabilities for databases, application servers, and packaged applications. BPEL PM and OSB are two compelling, market leading products that are driving Service-Oriented Architecture (SOA) implementation across enterprises. There is a lack of clarity around real-world operational use cases that would help operational administrators in their day-to-day tasks. Further, the documentation available online does not provide much information on administering BPEL PM and OSB with Enterprise Manager Grid Control efficiently. This book will help you set up the framework for managing operational tasks from a central location using Oracle Enterprise Manager Grid Control in a step-by-step functional approach. You will learn to automate various operational tasks that are essential for the smooth running of Oracle SOA products in production, thus increasing the efficiency of your SOA projects. This book shows how top-drawer management capabilities from Oracle Enterprise Manager Grid Control can be used to effectively manage your Oracle SOA environment. You start by discovering one or more BPEL and OSB components centrally. The book then explains how to monitor BPEL processes and OSB services, and how to get alerts on service availability and performance problems. It covers the management of BPEL and OSB infrastructure components and how to manage their configurations in a central repository. It follows a hands-on approach, showing you how to use an automated approach for deploying BPEL processes and OSB projects. By the end of this book, you will have learned several techniques to set up a framework that will help you manage your SOA environment from a central location. A step-by-step guide to using Enterprise Manager Grid Control to automate common operational tasks essential for the smooth running of Oracle SOA products such as BPEL Process Manager and Oracle Service Bus.
Keywords: Oracle (Computer file); Web services.; Business enterprises -- Computer networks -- Management.; elektronické knihy; electronic books